Similarities Between Medžela and the Common Property Code for Montenegro (Prilozi za orijentalnu filologiju, 2017)
The author compares the two codes in affect in Yugoslavia till 1945. He finds out important similarities between the two and explains them by the influence of the Islam law. Namely, the Turkish Civil Code (Medžela) was made according to the princip les of the Islam law, while the Common Property Law for Montenegro was made according to Montenegro customs which had in tum been influenced by the Islam law during the Turkish rule.